An educational program to improve self-care in heart failure patients - Dian Hudiyawati; Ida Imamah; Sulastri prihandini; Mazlinda Musa; Siti Mutiara Sari Dewi; Lia Astuti (Program Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Surakarta, 2025)
Knowledge of heart failure patients' self-care influences patient adherence and readiness for independent care at home. Self-care enhancement is a significant focus of heart failure management programs. Efforts can be made by providing self-care education using conventional media and the web. This study aimed to determine the effectiveness of web-based versus booklet-based self-care education in improving self-care behaviors among heart failure patients. Using a pretest-posttest experimental design, 76 eligible respondents were divided into two groups: a web-based education group and a booklet-based education group. The questionnaire used the Self-Care Heart Failure Index to measure the patient's self-care score. An Independent t-test was used to analyze differences in self-care scores in the two groups. Of 76 respondents in this study, >50% were male, and most were in the adult age range (36-55 years old). Based on the results of the independent t-test in both groups (web and booklet) showed a significant difference in the mean self-care score (p-value = 0.001). It illustrates that web media is more effective than booklet media. Providing education using media that health workers follow up is important to do as an effort to improve self-care in heart failure patients